Investigating polyol and acetic acid metabolism in wine related non-Saccharomyces yeasts - Mbuyane, Lethiwe Lynett (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScAgric)--Stellenbosch University, 2017.